CYCLIC RECRYSTALLIZATION OF FERRITE IN HOT-ROLLED LOW-CARBON SHEET STEEL WITH STRUCTURETEXTURAL HETEROGENEITY - A. M. Nesterenko; A. B. Sychkov; V. N. Tkach; V. I. Suhomlin (Литьë и металлургия)
It is determined that in the process of soaking at subcritical temperature 680 °C in hot-rolled rolling of low-carbon steel 08 ps recrystallization is developed with heterogeneous fu ll repeat change of the steel ferrite change by its section.